Key issues in regional growth and integration in Southern Africa - Arndt, Channing; Roberts, Simon J. (Informa UK Limited, 2018)
The decade to 2015 saw rapid growth in trade between Southern African Development Community (SADC) countries. Much of this growth reflected South African exports to its neighbours of diversified manufactured goods to meet growing urban consumption and to supply inputs to mining and infrastructure. While most SADC countries, aside from South Africa, grew quite rapidly over this period, their exports remained oriented to a narrow range of minerals and agricultural commodities destined to go outside the region. Drawing from a series of sectoral studies, we assess key regional issues including the investment and production decisions of firms whose operations stretch across borders, and consider the implications for a bottom-up integration agenda that could build productive capabilities across countries. Our evaluation highlights the importance of the spread of supermarkets, the need to address transport and logistics, and value chains whose competitive advantages are inherently regional, as in the cases of poultry and mining.